Correction of the functional condition of the bile excretory system in pathogenetic management of polymorbid patients with atherosclerosis - I. A. Gorbacheva; Ju. A. Sycheva; I. V. Kyrdyumov; L. P. Egorova; O. V. Makhiaylova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The aim of the search was development of some methods for improvement of effectiveness of treatment of polymorbid patients with atherosclerosis and disordered bile outflow. Complex phytotherapy (phytocomplex «Hepar») with its hepatoprotective and choleratic effects was prescribed for 33 patients with atherosclerosis and hepatobiliary dysfunction (in addition to dietotherapy and choleratics). Administration of the balanced phytotherapy resulted in significant reduction of the cholesterol level associated with the decrease of the C-reactive protein index in the blood. These changes were followed by decrease of the blood lipids and protein substrates oxidation - the factors meaning suppression of the degree of oxidative stress and of inflammation in the body.